2007
DOI: 10.1097/cmr.0b013e328194f265
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pathways to diagnose melanoma: a population-based study

Abstract: To better understand the clinical diagnostic process for invasive melanoma in Queensland. Descriptive population-based study of Queensland residents (n=3772) aged 20-75 years diagnosed with invasive melanoma between January 2000 and December 2003. Information was obtained via telephone interview combined with pathology data from the Queensland Cancer Registry. About 85% of melanoma patients diagnosed in Queensland saw a general practitioner at least once during the process, most of these for the initial consul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Despite its importance, reasons for health-care and doctor's delay in MM have been only sparsely investigated. Earlier studies emphasized difficulties in diagnostics [5, 13], as well as low access to general practitioners (GPs) [14], and gatekeeping [11]. Baade et al [13] have described the diagnostic process and highlighted the important role of GPs and the emerging role of primary care skin clinics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite its importance, reasons for health-care and doctor's delay in MM have been only sparsely investigated. Earlier studies emphasized difficulties in diagnostics [5, 13], as well as low access to general practitioners (GPs) [14], and gatekeeping [11]. Baade et al [13] have described the diagnostic process and highlighted the important role of GPs and the emerging role of primary care skin clinics.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies emphasized difficulties in diagnostics [5, 13], as well as low access to general practitioners (GPs) [14], and gatekeeping [11]. Baade et al [13] have described the diagnostic process and highlighted the important role of GPs and the emerging role of primary care skin clinics. They also reported that older people from rural areas needed special attention and intervention since both patient delay and health-care delay are prolonged.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Queensland, Australia, less than 20% of patients with melanoma see a dermatologist at any point in their care, relying instead principally on primary care physicians and surgeons. 7 However, detection of melanoma by a dermatologist, compared with detection by a nondermatology trained physician, has been associated with earlier melanoma detection and decreased mortality, highlighting the hazards of simply expanding the pool of providers evaluating patients for melanoma. 8 Other strategies have focused on improving access to dermatologists, rather than increasing the total number of providers.…”
mentioning
confidence: 98%
“…Several studies have described aspects of melanoma care in the Australian setting (18,19,22,(29)(30)(31)(32), or have measured compliance with clinical practice guidelines (21,(33)(34)(35)(36). However, to our knowledge our study is the first to report on doctors' knowledge of patients' risk factors and its relationship with subsequent skin-related follow-up advice and recommendations for melanoma in Australia.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%